2021
DOI: 10.1002/csc2.20358
|View full text |Cite
|
Sign up to set email alerts
|

Development of near‐infrared reflectance spectroscopy calibration for sugar content in ground soybean seed using Perten DA7250 analyzer

Abstract: There is growing interest in developing calibrations for soybean [Glycine max (L.) Merr.] seed sugars on near-infrared reflectance spectroscopy (NIRS) instruments to increase the efficiency of sugar profiling. In this study, a set of 253 samples from Virginia Tech's soybean germplasm with a wide range of sugar content were used to create prediction models for sucrose, raffinose, and stachyose in ground soybean seed on the Perten DA7250 NIRS instrument. Following acquisition of spectral data, seed sugars were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…We modified the extraction and quantification of sugars using high‐performance liquid chromatography (HPLC) described in Lord et al (2021). We weighed 10 mg of dried fecal sample and added 1 mL of HPLC water as the extraction solvent.…”
Section: Methodsmentioning
confidence: 99%
“…We modified the extraction and quantification of sugars using high‐performance liquid chromatography (HPLC) described in Lord et al (2021). We weighed 10 mg of dried fecal sample and added 1 mL of HPLC water as the extraction solvent.…”
Section: Methodsmentioning
confidence: 99%
“…After centrifugation, 100 μL of the supernatant was mixed with 900 μL of 65% ACN and filtered through a 0.2 μm membrane into an HPLC sample vial. The concentrations of sucrose, stachyose, and raffinose were determined using HPLC in accordance with Lord et al., 2021 . Three samples were tested for each genotype, and each sample underwent two technical replicates.…”
Section: Methodsmentioning
confidence: 99%
“…A prior study by Vandecasteele et al (2011) suggested a potential negative correlation between seed vigor traits and the sucrose/raffinose ratio in the legume plant Medicago truncatula. Sucrose, raffinose, and stachyose were extracted from 17 genotypes to assess possible effects on germination (Lord et al, 2021). In brief, seeds were initially ground to a fine powder using a water-cooled grinder.…”
Section: Seed Sugar Quantification Of the Seventeen Genotypesmentioning
confidence: 99%